PERSPEKTIF PELAKU USAHA DAN KONSUMEN KEDAI KOPI DI KOTA BANDUNG TERHADAP TREN CAFÉ-HOPPING - Aulia, Risma Namira; Wiyono, Sulistyodewi Nur (Universitas Galuh, 2023)
Changes in coffee consumption patterns have led to an increase and development in the coffee shop industry. The emergence of the cafe-hopping trend has necessitated continuous innovation in coffee shops. This research aims to understand the perspectives of coffee shop business owners and consumers regarding the cafe-hopping trend. The study used a sample of 169 individuals selected randomly through simple random sampling technique, and two informants were purposively selected to provide in-depth insights into the trends, developments, challenges, and opportunities in the coffee shop business. The data collection method involved interviews with coffee shop business owners for descriptive analysis. The research findings indicate that from the perspective of business owners, the cafe-hopping trend signifies high competition in the coffee industry. While it can increase exposure for coffee shops, it also carries the potential risk of losing regular customers and reducing customer loyalty. From the consumer's perspective, the cafe-hopping trend encourages the desire to explore new places and gain new experiences.